Mi i naši, oni i njihovi u politici: osobne deikse u govorima hrvatskih saborskih zastupnika: Goranka Blagus Bartolec (Stanje in perspektive uporabe govornih virov v raziskavah govora, 2024)
We and Ours, They and Theirs in Politics: Person Deixes in the Speeches of Croatian Parliamentarians. As units of reference that refer to real content and circumstances (persons, society, space, time, discourse), deixes are part of the language structure that enable the participants of a communication event to position themselves according to the circumstances of the utterance. The paper analyses the use of the pronouns we and ours, they and theirs as person deixes in the speech of Croatian parliamentarians using the ParlaMint-HR 2.0 corpus 2016–2020, which is publicly available on the NoSketch Engine tool. A politician in political speeches usually speaks in the first person plural, and his political argumentation is, in principle, based on the views of the social group he represents or to which he is ideologically inclined. The aim of the paper is to describe the syntactic and semantic features of person deixes in the speeches of parliamentarians with regard to the referents they refer to, and to determine to what extent the use of person deixes is based on the prototypical image of us and them as polarised parties, and in which we/ours and they/theirs are equal, i.e. the deixis we posits itself as a subject that protects or sides with the referents covered by the deixis they. Kao upućivačke jedinice deikse su sastavnica jezične strukture koje sudionicima komunikacijskoga događaja omogućuju da se postave prema okolnostima iskaza (osobe, društvo, prostor, vrijeme, diskurs). U radu se analizira upotreba zamjenica mi i naši, oni i njihovi kao osobnih (personalnih) deiksa u govoru hrvatskih saborskih zastupnika prema potvrdama iz korpusa ParlaMint-HR 2.0 (Croatian parliament) 2016–2020 dostupnom na korpusnoj platformi (No)Sketch Engine. Političar kao pojedinac u političkim govorima najčešće govori u prvom licu množine te se persuazivnost i intencionalnost njegove političke argumentacije u načelu temelji na stavovima društvene skupine koju predstavlja ili kojoj se ideološki priklanja. Cilj je rada opisati sintaktička i značenjska obilježja osobnih deiksa u govoru saborskih zastupnika s obzirom na referente na koje upućuju te utvrditi koliko se upotreba osobnih deiksa temelji na prototipnoj slici nas i njih kao polariziranih strana, a u kojoj su mjeri mi/naši i oni/njihovi ravnopravni, odnosno mi se postavlja kao subjekt koji štiti ili je na strani referenata obuhvaćenih deiksom oni.